Motivation for public service : perspective of self-determination theory (SDT) - Xu, Chengwei (2017)
This thesis consists of three self-contained essays on motivational studies. In the first essay, I review and reflect on the existing literature that addresses the motivation for public service, and then debate the definitions of public service motivation (PSM) with relative concepts such as prosocial motivation, altruism, values, beliefs, attitudes, etc. Public service motivation (PSM), “the motivation to serve the public,” is a form of prosocial motivation. It was proposed in 1990 as a major research theme in public administration within the scope of altruism. PSM refers to people’s commitment to public interest, compassion, and interest in policy making. However, this is misleading as prosocial motivation is never purely altruistic in nature. For example, many high ranking public officials make public policies simply due to media pressure or public scrutiny. Therefore, I use the motivational typology in the Self-Determination Theory (SDT) to debate the multi-dimension of motivation for public service. Based on SDT, a new construct, the motivation for public service (MPS), is proposed to analyze public employees’ motivations. Our new SDT-based approach shows that there cannot be a universal measurement tool for motivations. Scholars need to first identify a given public service behavior, and then develop measures for intrinsic motivation, identified regulation, introjected regulation, and external regulation for this behavior.